Anatomical location of LPA1 activation and LPA phospholipid precursors in rodent and human brain. (27th April 2015) - González de San Román, Estibaliz; Manuel, Iván; Giralt, María Teresa; Chun, Jerold; Estivill‐Torrús, Guillermo; Rodríguez de Fonseca, Fernando; Santín, Luis Javier; Ferrer, Isidro; Rodríguez‐Puertas, Rafael
Abstract Lysophosphatidic acid (LPA) is a signaling molecule that binds to six known G protein‐coupled receptors: LPA1–LPA6. LPA evokes several responses in the CNS, including cortical development and folding, growth of the axonal cone and its retraction process. Those cell processes involve survival, migration, adhesion proliferation, differentiation, and myelination. The anatomical localization of LPA1 is incompletely understood, particularly with regard to LPA binding. Therefore, we have used functional [35S]GTPγS autoradiography to verify the anatomical distribution of LPA1 binding sites in adult rodent and human brain. The greatest activity was observed in myelinated areas of the white matter such as corpus callosum, internal capsule and cerebellum. MaLPA1‐null mice (a variant of LPA1‐null) lack [35S]GTPγS basal binding in white matter areas, where the LPA1 receptor is expressed at high levels, suggesting a relevant role of the activity of this receptor in the most myelinated brain areas. In addition, phospholipid precursors of LPA were localized by MALDI‐IMS in both rodent and human brain slices identifying numerous species of phosphatides and phosphatidylcholines. Both phosphatides and phosphatidylcholines species represent potential LPA precursors. The anatomical distribution of these precursors in rodent and human brain may indicate a metabolic relationship between LPA and LPA1 receptors. Lysophosphatidic acid (LPA) is a signaling molecule that binds to six known G protein‐coupled receptors (GPCR), LPA1 to LPA6. LPA evokes several responses in the central nervous system (CNS), including cortical development and folding, growth of the axonal cone and its retraction process. We used functional [35S]GTPγS autoradiography to verify the anatomical distribution of LPA1‐binding sites in adult rodent and human brain. The distribution of LPA1 receptors in rat, mouse and human brains show the highest activity in white matter myelinated areas. The basal and LPA‐evoked activities are abolished in MaLPA1‐null mice. The phospholipid precursors of LPA are localized by MALDI‐IMS. The anatomical distribution of LPA precursors in rodent and human brain suggests a relationship with functional LPA1 receptors.